EFFECT OF CUTTINGS COLLECTION TIMES, LENGTHS AND PLANTING METHODS IN PROPAGATION AND GROWTH OF Salix acmophylla Bioss - Muthafar O. Abdullah (Mesopotamia Journal of Agriculture)
This study was carried out at Ninevah plantation Nursery in Mosul city, during the period from mid January to the end of October (1999) to investigate the effect of four collection times, and four cutting lengths, using tow planting methods (Vertical and Horizontal) in propagation of Salix seedlings. This experiment conducted as factorial experiment in Randomize of completely Block Design with three factors and three blooks. At the end of the experiment number of branches, number of leaves, leave area and dry weight of the stem, branches and leaves was studies. The results showed that the collection time (15 February), cutting length (30 cm.) and vertical planting method was the best and it gave higher means for all studied characteristics. The result also showed that the following interaction between (collection cutting time 15 February and cutting length 30 cm.), (collection cutting time 15 February and vertical planting method), (cutting length 30 cm. and vertical planting method) and among (collection cutting time 15 February and cutting length 30 cm. and vertical planting method) were the best among other interactions.